THE INFLUENCE OF TAXPAYER AWARENESS AND TAXPAYER COMPLIANCE ON THE IMPLEMENTATION OF THE VOLUNTARY DISCLOSURE PROGRAM (PPS) AT THE KPP PRATAMA RUNGKUT IN SURABAYA - Yunita, Asmiasih; Andayani, Sari (Yayasan Education and Social Center, 2023)
This study aims to investigate the impact of tax knowledge, taxpayer awareness, and taxpayer compliance on the successful implementation of the Voluntary Disclosure Program (PPS) at the Rungkut Pratama Tax Office in Surabaya. In the focus of this study, the population of concern is individual taxpayers who actively participate in the Voluntary Disclosure Program in the region. Through simple random sampling techniques, the total number of samples used in this study was recorded as many as 96 individual taxpayers. The method used in this study is Smart-PLS, a path analysis method based on SEM (Structural Equation Modeling) that provides a framework for analyzing the relationship between the variables in the model. By utilizing this instrument, this study aims to understand more deeply how the variables of tax knowledge, taxpayer awareness, and taxpayer compliance interact. It can influence the effectiveness and outcomes of the Voluntary Disclosure Program. The results obtained from the analysis of this study illustrate exciting findings. Firstly, surprisingly, taxpayers' awareness level does not significantly impact the success rate of the Voluntary Disclosure Program (PPS) in this region. However, these results raise further questions about other factors that may have influenced taxpayer attitudes and participation in the program.